2004
DOI: 10.1007/s00253-003-1407-3
|View full text |Cite
|
Sign up to set email alerts
|

A derivative of the menaquinone precursor 1,4-dihydroxy-2-naphthoate is involved in the reductive transformation of carbon tetrachloride by aerobically grown Shewanella oneidensis MR-1

Abstract: Transformation of carbon tetrachloride (CT) by Shewanella oneidensis MR-1 has been proposed to involve the anaerobic respiratory-chain component menaquinone. To investigate this hypothesis a series of menaquinone mutants were constructed. The menF mutant is blocked at the start of the menaquinone biosynthetic pathway. The menB, menA and menG mutants are all blocked towards the end of the pathway, being unable to produce 1,4-dihydroxy-2-naphthoic acid (DHNA), demethyl-menaquinone and menaquinone, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The fact that menaquinone rescued reduction of the Fe-beads by a menF mutant of MR-1 but did not stimulate Fe-bead reduction by wild-type cells demonstrated that the mediator used for iron reduction at a distance is not a product of the menaquinone biosynthetic pathway. This rules out the previously described quinone-like molecule derived from the menaquinone pathway (48,67) as an electron shuttle for iron reduction at a distance.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that menaquinone rescued reduction of the Fe-beads by a menF mutant of MR-1 but did not stimulate Fe-bead reduction by wild-type cells demonstrated that the mediator used for iron reduction at a distance is not a product of the menaquinone biosynthetic pathway. This rules out the previously described quinone-like molecule derived from the menaquinone pathway (48,67) as an electron shuttle for iron reduction at a distance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of radionucleotide oxides can be reduced (Myers and Nealson, 1988;Nealson and Scott, 2003;Icopini et al, 2009). Thus, bacteria such as Shewanella significantly impact biogeochemical cycling processes and are of particular interest with regard to bioremediation processes (Heidelberg et al, 2002;Nealson et al, 2002;Lovley et al, 2004;Ward et al, 2004;Hau and Gralnick, 2007). It has been hypothesized that direct interaction of Shewanella cells with, or close proximity to, an appropriate surface facilitates the deposition of electrons (Das and Caccavo, 2000;Gorby et al, 2006;McLean et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported a genetic analysis of surface adhesion and biofilm formation, as well as a physiological and molecular characterization of detachment in Shewanella oneidensis MR-1, which is a facultative Fe(III) and Mn(IV) mineral-reducing soil bacterium and plays a critical role in mineral dissolution, heavy-metal (im)mobilization, and pollution degradation (31,33,47,48,52). In a genetic screen for biofilm defective mutants, we identified type IV pili as critical in mediating the initial adhesion of cells to the substratum during surface colonization (47).…”
mentioning
confidence: 99%